Differentiation between Plasminogen Activators by Means of Epsilon- Aminocaproic Acid - Kok, P; Astrup, T (Thrombosis and Haemostasis, 1972)
The differentiation between plasminogen activators from tissue and urine by means of the patterns of inhibition produced by epsilon-aminocaproic acid (EACA) in fibrin plate assays was investigated. Different inhibition patterns reflected genuine differences between two types of activators. The method allows the differentiation between two types of activators in weakly fibrinolytic and impure activator solutions.A biphasic pattern of inhibition by EACA was observed with human urine as well as with the purified urokinase preparations. The degree of enhancement of fibrinolysis observed in the millimolar concentration range of EACA fluctuated with the fibrin substrate and was, in part, related to its plasminogen content. Increasing concentrations of EACA produced a uniformly increasing inhibition of preparations of tissue activator obtained in various degrees of purity from porcine ovary and heart. Plasmin was uniformly inhibited by EACA. Inhibition of plasmin required about 100 times higher concentrations of EACA than inhibition of tissue activator-induced fibrinolysis. EACA produced a slightly biphasic pattern of inhibition with plasminogen activator from human uterine tissue.